Arte y contexto. Una mirada social desde la intervención artística. - Reyes Piedra, Maricela Beatriz (2016)
The following research seeks to demonstrate through an artistic intervention the socio-cultural problem that causes illegal migration within the margin of Ecuadorian households, encompassing both the people who leave the country and the families who are waiting for them. The economic problems that have existed in the country in previous years, added to the current ones, are to a greater extent those that have generated this problem, becoming over time, one of the most popular social ills today. What is troubling about all this is that the migrant leaving home and breaking into a foreign country, understands that there is a possibility that he will not return, and even so he does, and by the time he calculates the possible harmful effects, it is already too much Late, from children who can remain in orphanhood, exposed to all kinds of vicissitudes, and without advice that serves as a filter, when they must differentiate between good and evil, they could be condemned to a criminal life. Even families who live with the uncertainty of whether the changes, already intermixed in their daily lives will be permanent or only temporary, in short, an affected family, which is very unfortunate because the home is the basis of the general behavior of a society. For this reason, it is necessary to adopt a position, a side, and from there pragmatism will guide the most viable and immediate action, one that is aimed at mutating that adventitious adventurous thought proper to the desperate, and that forces the migrant potential to take a Little more time to evaluate what for him is better in the long term, to leave aside the unreason, to think about the evils that could afflict his family should he fail in his outlandish company, which by its clandestine nature is Inevitably subject to being swindled with some sum of money, by the so-called coyotes, however small it may be harmful, and in the worst case, it could very well lose its own life. This is how the artistic intervention is chosen as a medium, in the eagerness to take what has been said and return it with added value for the spectator, in order to raise awareness, understanding the urgent need for information placed at the service of the average Ecuadorian. The work in general is made up of two bodies, two graphic works, the first of a road sign, and the second, a video art that allows to approach the subject with greater visual and argumentative richness, with the idea in mind of being more persuasive And leave a mark on contemporary art. To do this, a real case will be presented, on a minor and his father, separated for nine years, because of the migration of the latter to American lands. Janina, that is the name of the girl on whom all this work is revolving, to the present date she is only ten years old, and it is proposed the possibility, within the format of this project, to create those yellow lines interspersed in the Half of the road used to separate one lane from another, but which, in particular, she will use as an extension of herself, with an obvious surrealistic tint, and whose goal is to reach as far as Mario , His father, in order to do what he has not done in almost a decade, which is to play it, hence the artistic work is named, "as if they could touch" that said incidentally, has the participation Physics of the aforementioned, so that it will be enriched with expressions and body language very sincere.